Zygmunt Bauman and the West a sociology of intellectual exile - Palmer, Jack Dominic (McGill-Queen's University Press, 2023)
"Zygmunt Bauman was both an outsider of Western modernity and one of its foremost interpreters. He was an exemplary figure in twentieth-century intellectual work on exile who experienced both Nazi and Soviet forms of totalitarianism. The first work to draw extensively on Bauman's personal archive, Zygmunt Bauman and the West argues that the distinctive social thought that sprung from Bauman's lived experiences of exile amounts to a sustained, sophisticated, and hitherto unappreciated problematisation of Eurocentrism and the West. Through an overview of the intellectual's thought and his contribution to sociology, Jack Palmer explores Bauman's experience and interpretation of the West and seeks to understand his work in a broader context, outside of the Eurocentric environment from which it was born. Intervening in a resurgent sociology of intellectuals, Zygmunt Bauman and the West reevaluates the place of the West in social and political thought."--
Keywords: Bauman, Zygmunt -- 1925-2017; Eurozentrismus; Soziologie; Exil; Bauman, Zygmunt / 1925-2017; Sociology; Civilization, Western / 20th century; Sociologie; Civilisation occidentale / 20e siècle; sociology; Civilization, Western; 1900-1999